From the Editor - Disthabanchong, Sinee (Journal of the Nephrology Society of Thailand, 2023)
It has been one year since I was assigned the role of being the editor-in-chief of Journal of the Nephrology Society of Thailand. In the past year, the editorial team has transformed the journal into a fully online format. Each article now has its own HTML version, and PDF files of each article can be downloaded. Articles published in the journal can now be found through Google search by title, keywords, and author names. Additionally, an online submission and peer review system has been established to meet international peer-review journal standards, and the journal is now able to be published on time. Most importantly, the editorial team is planning to include the journal in the Thailand citation index in the coming year. In this final issue of the year, we have included a section on the executive summary of clinical practice guidelines developed by the Nephrology Society of Thailand, which has been published in full last year. The purpose of the publication is to make the information accessible to everyone and to serve as a reference for citations. The journal plans to publish the executive summary of clinical practice guidelines developed by the Nephrology Society of Thailand in the final issue of each year. Lastly, I hope that Journal of the Nephrology Society of Thailand will continue to be a sustainable source for academic articles related to kidney diseases. It is an excellent option for both local and international scientists to submit their research for publication, providing a platform for disseminating new knowledge that can be recognized and accessed worldwide. As we enter the New Year of 2024, I wish all of you who care for kidney disease patients much happiness and prosperity.